High-resolution nanomechanical analysis of suspended electrospun silk fibers with the torsional harmonic atomic force microscope - Cronin-Golomb, Mark; Sahin, Ozgur (Beilstein Journal of Nanotechnology, 2013)
Atomic force microscopes have become indispensable tools for mechanical characterization of nanoscale and submicron structures. However, materials with complex geometries, such as electrospun fiber networks used for tissue scaffolds, still pose challenges due to the influence of tension and bending modulus on the response of the suspended structures. Here we report mechanical measurements on electrospun silk fibers with various treatments that allow discriminating among the different mechanisms that determine the mechanical behavior of these complex structures. In particular we were able to identify the role of tension and boundary conditions (pinned versus clamped) in determining the mechanical response of electrospun silk fibers. Our findings show that high-resolution mechanical imaging with torsional harmonic atomic force microscopy provides a reliable method to investigate the mechanics of materials with complex geometries.
Keywords: atomic force microscopy; nanomechanical characterization; silk fibers; tissue scaffolds; torsional harmonic cantilevers

(untitled) - García, R.; Magerle, R.; Perez, R. (Nat. Mater., 2007)

(untitled) - Balke, N.; Jesse, S.; Morozovska, A. N.; Eliseev, E.; Chung, D. W.; Kim, Y.; Adamczyk, L.; García, R. E.; Dudney, N.; Kalinin, S. V. (Nat. Nanotechnol., 2010)

(untitled) - Dokukin, M. E.; Guz, N. V.; Gaikwad, R. M.; Woodworth, C. D.; Sokolov, I. (Phys. Rev. Lett., 2011)

(untitled) - Dong, M.; Sahin, O. (Nat. Commun., 2011)

(untitled) - Forchheimer, D.; Platz, D.; Tholén, E. A.; Haviland, D. B. (Phys. Rev. B, 2012)

(untitled) - Garcia, R.; Herruzo, E. T. (Nat. Nanotechnol., 2012)

(untitled) - Jesse, S.; Kalinin, S. V.; Proksch, R.; Baddorf, A. P.; Rodriguez, B. J. (Nanotechnology, 2007)

(untitled) - Martínez, N. F.; Lozano, J. R.; Herruzo, E. T.; Garcia, F.; Richter, C.; Sulzbach, T.; Garcia, R. (Nanotechnology, 2008)

(untitled) - Platz, D.; Tholén, E. A.; Pesen, D.; Haviland, D. B. (Appl. Phys. Lett., 2008)

(untitled) - Proksch, R. (Appl. Phys. Lett., 2006)

(untitled) - Raman, A.; Trigueros, S.; Cartagena, A.; Stevenson, A. P. Z.; Susilo, M.; Nauman, E.; Contera, S. A. (Nat. Nanotechnol., 2011)

(untitled) - Sikora, A.; Bednarz, L. (Cent. Eur. J. Phys., 2011)

(untitled) - Solares, S. D.; Chawla, G. (J. Appl. Phys., 2010)

(untitled) - Tetard, L.; Passian, A.; Thundat, T. (Nat. Nanotechnol., 2010)

(untitled) - Tetard, L.; Passian, A.; Venmar, K. T.; Lynch, R. M.; Voy, B. H.; Shekhawat, G.; Dravid, V. P.; Thundat, T. (Nat. Nanotechnol., 2008)

(untitled) - Xu, X.; Melcher, J.; Basak, S.; Reifenberger, R.; Raman, A. (Phys. Rev. Lett., 2009)

(untitled) - Abak, M. K.; Aktas, O.; Mammadov, R.; Gürsel, I.; Dâna, A. (Appl. Phys. Lett., 2008)

(untitled) - Hutter, C.; Platz, D.; Tholén, E. A.; Hansson, T. H.; Haviland, D. B. (Phys. Rev. Lett., 2010)

(untitled) - Lozano, J. R.; Garcia, R. (Phys. Rev. Lett., 2008)

(untitled) - Sahin, O.; Magonov, S.; Su, C.; Quate, C. F.; Solgaard, O. (Nat. Nanotechnol., 2007)

(untitled) - Sarioglu, A. F.; Solgaard, O. (Appl. Phys. Lett., 2008)

(untitled) - Solares, S. D.; Hölscher, H. (Nanotechnology, 2010)

(untitled) - Stark, M.; Stark, R. W.; Heckl, W. M.; Guckenberger, R. (Proc. Natl. Acad. Sci. U. S. A., 2002)

(untitled) - Stark, R. W.; Naujoks, N.; Stemmer, A. (Nanotechnology, 2007)

(untitled) - Platz, D.; Forchheimer, D.; Tholén, E. A.; Haviland, D. B. (Nat. Commun., 2013)

(untitled) - Williams, J. C.; Solares, S. D. (Beilstein J. Nanotechnol., 2013)

(untitled) - Cronin-Golomb, M.; Murphy, A. R.; Mondia, J. P.; Kaplan, D. L.; Omenetto, F. G. (J. Polym. Sci., Part B: Polym. Phys., 2012)

(untitled) - Ihalainen, P.; Järnström, J.; Määttänen, A.; Peltonen, J. (Colloids Surf., A, 2011)

(untitled) - Leung, K. M.; Wanger, G.; Guo, Q.; Gorby, Y.; Southam, G.; Lau, W. M.; Yang, J. (Soft Matter, 2011)

(untitled) - Qu, M.; Deng, F.; Kalkhoran, S. M.; Gouldstone, A.; Robisson, A.; Van Vliet, K. J. (Soft Matter, 2011)

(untitled) - Sahin, O.; Erina, N. (Nanotechnology, 2008)

(untitled) - Schön, P.; Dutta, S.; Shirazi, M.; Noordermeer, J.; Vancso, G. J. (J. Mater. Sci., 2011)

(untitled) - Sweers, K.; van der Werf, K.; Bennink, M.; Subramaniam, V. (Nanoscale Res. Lett., 2011)

(untitled) - Wang, S.; Zhao, G. (Mater. Lett., 2012)

(untitled) - Li, C.; Vepari, C.; Jin, H.-J.; Kim, H. J.; Kaplan, D. L. (Biomaterials, 2006)

(untitled) - Sahin, O. (Rev. Sci. Instrum., 2007)

(untitled) - Belov, M.; Quitoriano, N. J.; Sharma, S.; Hiebert, W. K.; Kamins, T. I.; Evoy, S. (J. Appl. Phys., 2008)

(untitled) - Wang, M.; Jin, H.-J.; Kaplan, D. L.; Rutledge, G. C. (Macromolecules, 2004)